2012
DOI: 10.1007/s10067-012-1948-x
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of cutaneous microcirculatory status of Kawasaki disease

Abstract: Kawasaki disease (KD) is associated with generalized vasculitis with a predilection for coronary artery leading to ectasia and aneurysm in some cases. The aim of this study was to noninvasively assess the cutaneous microcirculation and correlate it with the coronary artery diameter in these patients. Laser Doppler flowmetry and dynamic capillaroscopy were performed at the nailbeds to assess total cutaneous blood flow and microcirculation in children with KD, both in the afebrile phase (after the resolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Coronary arteries are involved in the majority of cases, and aneurysms are the major manifestation of the disease. A study of 64 children with Kawasaki disease reported capillary morphologic abnormalities both in the afebrile and convalescent phases of disease, including an increased diameter of the arterial and venous limbs, a higher intercapillary distance, and a decrease in the loop numbers ().…”
Section: Capillaroscopy In Other Childhood Diseasesmentioning
confidence: 99%
“…Coronary arteries are involved in the majority of cases, and aneurysms are the major manifestation of the disease. A study of 64 children with Kawasaki disease reported capillary morphologic abnormalities both in the afebrile and convalescent phases of disease, including an increased diameter of the arterial and venous limbs, a higher intercapillary distance, and a decrease in the loop numbers ().…”
Section: Capillaroscopy In Other Childhood Diseasesmentioning
confidence: 99%
“…Skin covers the body and is known as the largest organ in the human and the most important role is its barrier functions. 13,14 Previously study had approved microcirculation of skin is related to systemic disease, such as systemic sclerosis, 15 Kawasaki disease, 16 polycystic ovary syndrome, 17 burn scar, Bell's palsy, and acute radio dermatitis. [18][19][20] Our study confirmed that blood flow in different cutaneous regions varied.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study about Kawasaki disease and NFC was found and it involved 64 pediatric patients [44]. Microcirculation abnormalities found included reduced density, dilation of arterial and venous limb diameters, higher intercapillary distance, and abnormal loops.…”
Section: Medium Vessel Vasculitismentioning
confidence: 99%